Relationship Of Protein Intake And Stunting Events In Children - Tenriwati; Asnidar; Astika Dwi Fitriani (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2019)
Stunting or short body is one of the nutritional problems that are of global concern especially developing countries including Indonesia, and Indonesia ranked fifth with the level stunting events in the world. Many factors that cause stunting are one of them lack of food intake obtained by someone and inadequate such as lack of food intake someone and inadequate such as lack of energy and protein in taking. The purpose of the study is to know the relationship between protein intake and the incidence of stunting in children in the work area of public health Bontobangun Rilauale sub-district Bulukumba district. The research design was analytic observational with a cross-sectional approach. population and sample in this study were children aged 2-7 years as many as 47 respondents were taken using nonprobability sampling technique using observation sheet and food recall the results showed that there was a relationship between protein intake and the incidence of stunting in the work area Bontobagun community health center builds rural districts Bulukumbain 2018 with chi-square alternative fisher test obtained p-value = 0,000 (<Î±=0,05. It is suggested that the results of this study can be used as scientific reading material in the library and can also be used as reference material for students who research similar problems.